Enhancement of uranium ion flux by consecutive extraction via hollow fiber supported liquid membrane - Lothongkum, A. W.; Ramakul, P.; Sasomsub, W.; Laoharochanapan, S.; Pancharoen, U. (My University, 2009)
The enhancement of uranium separation from trisodium phosphate, a by-product, from monazite processing through a supported liquid membrane system by a consecutive extraction using the synergistic extractants is first time demonstrated in this work. Feed solution was trisodium phosphate solution containing uranium ions of 45 ppm, and the stripping solution was nitric acid solution. The effects of types and concentrations of the extractants, concentration of HNO3, flow rates of feed and stripping solutions and the numbers of cycles on extraction efficiency were investigated. D2EHPA, Cyanex 923, TBP, TOA and Aliquat 336 dissolved in kerosene were used as the extractants. The results showed that by using the synergistic extractant of Aliquat 336 mixed with TBP, the percentages of extraction and stripping or recovery considerably increased higher than those obtained by a single extractant. For the seventh-cycle separation by one-module operation using 0.1 M Aliquat 336 and 0.06 M TBP mixture, 0.5 M HNO3, and equal flow rates of feed and stripping solutions at 100 mL/min, the percentages of extraction and stripping reached 99 and 53 in 350 min. The amount of uranium ions remaining in trisodium phosphate solution was 0.22 ppm, which stayed within the standard value of technical grade trisodium phosphate of 3 ppm. © 2009 Taiwan Institute of Chemical Engineers.
Keywords: Hollow fiber; Liquid membrane; Synergistic extraction; Trisodium phosphate; Uranium